Willingness to pay for renewable energy : evidence from Malaysian’s households - A.A. Azlina; Mahirah Kamaludin; Moe, Shwe Sin (Penerbit Universiti Kebangsaan Malaysia, 2018)
The growing consumption of fossil energy fuels that is linked with climate change and quality of life has pushed renewable energy development into the centre of debate on energy security. Renewable energy has become a top priority for the governments in most countries due to its distinctive features of a cleaner energy source. Despite Malaysia’s effort to encourage the various forms of renewable energy (RE), the total amount of RE is still very low. Moreover, difficulties arise as the energy supply is highly related to the general wellbeing of the individuals and societies. As such, exploring the consumer’s willingness for RE has become vital as this new knowledge can be used by the government to promote long run RE consumption. This study attempts to investigate consumers’ WTP for RE sources and discover other factors of WTP with special attention to Malaysia setting. By employing a contingent valuation method (CVM), the findings reveal that the willingness to pay (WTP) for RE is significantly related to the proposed bid price and household income. The results also indicate that consumer on average is willing to pay about RM3.22 (USD0.82) per month for the Renewable Energy Fund. This micro-level investigation can be a useful framework in organising information on how consumers are willing to contribute towards the development of RE in Malaysia.